The Gentlemanly Order & the Politics of Production in the Transition to Capitalism in the Home District, Upper Canada - Schrauwers, Albert (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2010)
Abstract Few have examined the class politics of pre-Rebellion Toronto in any detail; a vocabulary of class born in an industrial setting appears poorly fitted to an agrarian colony where production took place in small workshops of independent journeymen and apprentices under the supervision of master craftsmen. This article, in contrast, examines the transformations in class relations of the period in a framework derived from Cain & Hopkins theory of “Gentlemanly Capitalism.” It examines the creation of the three “fictitious commodities” (money, land, and labour) that Polanyi places at the heart of the “Great Transformation” in the context of the “Gentlemanly Order” being constructed by Upper Canada’s elite. This Gentlemanly Order was corporate in nature. The article concludes with an analysis of class conflict that resulted in the era, in particular in the building trades, where workers helped form a province-wide “Mechanics Association.”